(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2007)
Rapid modernization and exponential sophistication have taken place over the last few years in the field of medical sciences. These undoubtedly have increased longevity and relief from sickness but a lot is desired to be done with regard to handling care and attention to those who are sick and even to those who are dead & need to be laid to rest and peace with dignity and respect. Many people, when they are in the hospital, find that their minds turn quite naturally to such questions as, "Why is there sickness?" "Why did this happen to me?" "Am I being punished?" "What is the meaning of life?" These questions are religious questions. Should such questions come to your mind, you might find comfort in the words of chaplains. Excellent and close working relationship with architects, engineer’s project supervisor and administrative manager could lead to a successful facility and not the usual hospital atmosphere of fear and dislike so that even the most reluctant visitors would not mind entering the hospital complex.